Physicochemical surface properties of bacterial cellulose/polymethacrylate nanocomposites: an approach by inverse gas chromatography - Faria, Marisa (2019)
Nanocomposites of poly(glycidyl methacrylate) and bacterial cellulose (BC), or poly(poly(ethylene glycol) methacrylate) and BC were produced via the in-situ polymerization of methacrylic monomers, inside the BC 3D network. The nanocomposites surface properties were evaluated by inverse gas chromatography (IGC). The dispersive component of surface energy (γsd) varied between 35.64 - 83.05 mJ m-2 at 25 °C. The surface of the different nanocomposites has a predominant basic character (Kb/Ka = 4.20-4.31). Higher specific interactions with polar probes were found for the nanocomposite bearing pendant epoxide groups, that apart from the low surface area (SBET = 0.83 m2 g-1) and monolayer capacity (nm = 2.18 μmol g-1), exhibits a high value of γsd (88.19 mJ m-2 at 20 °C). These results confirm the potential of IGC to differentiate between nanocomposites with different surface functional groups and to predict their potential interactions with living tissues, body fluids and other materials.